Role Conflict And Role Ambiguity Among Malaysian Journalists In Newsroom Decision-Making - Ibrahim, Faridah (1995)

(untitled)
The main objective of the study was to determine the relationship between some selected independent variables with role conflict and role ambiguity perceived by Malaysian journalists in newsroom decision-making. The study was carried out among 226 randomly selected journalists from eight Malaysian print media organisations and a national news agency. A survey research method was employed and self-administered and structured questionnaires were used to collect data. Descriptive and inferential statistics, namely, frequency and percentage, Pearson's correlation coefficients, multiple regression and discriminant analysis were used for data analysis.